Anise and Fennel Essential Oils and Their Combination as Natural and Safe Housefly Repellents - Hataichanok Passara; Sirawut Sittichok; Cheepchanok Puwanard; Jirisuda Sinthusiri; Tanapoom Moungthipmalai; Kouhei Murata; Mayura Soonwera (My University, 2024)
Essential oils (EOs) are effective repellents and eco-friendly alternatives. We tested single and combination EOs of fennel and anise for repellency and stability against houseflies. All treatments were stored at 27 °C for up to 360 days. Efficacies were compared against α-cypermethrin as a reference. Safety bioassay used on two representative non-target species (guppies and earthworms) confirmed safety. The strongest repellency and stability, 100% repellency and RC50 of 0.4 mL/m3 on day 1, was achieved by a fennel + anise EO combination (1:1). After 360 days, these combinations remained effective (95% repellency), and RC50 = 0.8 mL/m3. The EO combinations were more effective than all single EOs and α-cypermethrin at all times, showing strong synergy with a synergistic repellent index of 2.4 to 3.3. This fennel + anise EO combination was more than 24 times more effective as a repellent than α-cypermethrin. Morphological damage included damaged antennae with twisted flagella and abnormal aristae. All single and combination EOs were not toxic to the non-targets and could be considered safe, whereas α-cypermethrin was highly toxic to them. Thus, the fennel + anise EO combination has great potential to be developed as a safe, natural repellent for managing housefly populations.
Keywords: Housefly; DEET; Insect Pest Control Strategies